Limelight - Chalin, Charles 1889-1977; Bloom, Claire 1931-; Keaton, Buster 1895-1966 (Centennial collection, 1952)
Set in London, in 1974, the film stars Chaplin as an aging music hall comic who's convinced he can no longer move people to laughter. But he gets a final opportunity to shine when he saves a young, equally desperate ballet dancer (Bloom) from suicide, then guides her to triumph on the stage.